The hidden life of love: The function of the Bible in Kierkegaard"s "Works of love" - Huls, Jos (HTS teologiese studies, 2011)
This article discussed the use of the Bible in ‘Love’s hidden life and its recognizability by its fruits’, which is the first reflection of Søren Kierkegaard’s book, Works of love. The article noted that in the first part of the reflection, Kierkegaard points out how easily love is ignored because of its hidden character and because it belongs to the realm of the heart. Consequently, it seems sagacious to trust only those things that we can observe with our senses. But this attitude speaks of self-deception and fear that will bring eternal loss, because it locks us out of love which connects us with the essence of God himself. The article then explained Kierkegaard’s argument that love produces fruit which has to be distinguished from other kinds of fruit. This distinction raises the question of discernment between forms that claim to be love and Christian love, which is rooted in eternity. The second part of this reflection focuses on love as the main feature of Kierkegaard’s anthropology that springs from the heart, has its origin in God and therefore cannot be penetrated by the tools of logic. This does not imply that we cannot live this love. On the contrary, we need to live it in order to become familiar with it and to understand it from within. However, this familiarity will, in the first place, confront us with love’s unfathomableness and its unfathomable connectedness with all existence. The more we become acquainted with the love of our heart, the more this love will lead us into the mystery of God’s eternity. A second feature of Kierkegaard’s anthropology, which is immediately linked to the first, is the acknowledgement that this love manifests itself as a need with roots in the hunger of the heart. For the purposes of this article, Kierkegaard’s use of the Bible in all these parts was analysed and a general perspective on his reception of the Bible was offered.